FERONIA receptor kinase interacts with S‐adenosylmethionine synthetase and suppresses S‐adenosylmethionine production and ethylene biosynthesis in Arabidopsis. (16th July 2015) - Mao, Dandan; Yu, Feng; Li, Jian; Van de poel, Bram; Tan, Dan; Li, Jianglin; Liu, Yanqionq; Li, Xiushang; Dong, Mengqiu; Chen, Liangbi; Li, Dongping; Luan, Sheng
Abstract: Environmental inputs such as stress can modulate plant cell metabolism, but the detailed mechanism remains unclear. We report here that FERONIA (FER), a plasma membrane receptor‐like kinase, may negatively regulate the S ‐adenosylmethionine (SAM) synthesis by interacting with two S ‐adenosylmethionine synthases (SAM1 and SAM2). SAM participates in ethylene, nicotianamine and polyamine biosynthetic pathways and provides the methyl group for protein and DNA methylation reactions. The A rabidopsis fer mutants contained a higher level of SAM and ethylene in plant tissues and displayed a dwarf phenotype. Such phenotype in the fer mutants was mimicked by over‐expressing the S ‐adenosylmethionine synthetase in transgenic plants, whereas sam1/2 double mutant showed an opposite phenotype. We propose that FER receptor kinase, in response to environmental stress and plant hormones such as auxin and BR, interacts with SAM synthases and down‐regulates ethylene biosynthesis. Highlighting: The receptor‐like kinase FERONIA, which plays important role in the plant development and environment response, can interacts with S‐adenosylmethionine (SAM) synthesis and down‐regulates SAM and ethylene biosynthesis.